MPC with Space Vector Phase-Shift PWM (SV-PSPWM) Technique with Harmonic Mitigation Strategy for Shunt Active Power Filters Based on H-Bridge Multilevel Converter - Renault, Alfredo; Pacher, Julio; Comparatore, Leonardo; Ayala, Magno; Rodas, Jorge; Gregor, Raul (Frontiers in Energy Research, 2022)
This article presents a shunt active power filter based on 7-level cascaded H-bridge converters. The main contribution is an enhanced control strategy that combines model-based predictive control, spacial vector modulation, pulse-width modulation displacement technique per phase and a sub-optimal control of the DC-link voltages. The proposed control scheme largely synthesizes the spacial voltage vectors using three-level converters as a base and then projecting for seven levels, reducing the redundant vectors of the control algorithm. In addition, the current harmonics on the power side network, caused by non-linear loads connected to the common coupling point, are compensated. On the other hand, the proposed sub-optimal control of the DC-link voltages achieves a balancing of the voltages of the capacitors of the nine converters by using minimum voltage sensors, one per phase. The experimental results confirmed the feasibility and efficacy of the proposed controller.